Home Fires and Hearth: One’s Place in this World, and How Art Can Make a Difference - Modeen, Mary (Te Kaharoa, 2009)
Ties between land and human identity, culture and adaptation to the environment are undeniably complex. This paper examines some aspects of these through art the effects of cultural history and philosophy typified in indigenous peoples generally, and Maori in particular.